The maedi-visna virus Tat protein induces multiorgan lymphoid hyperplasia in transgenic mice. - Vellutini, C (1994)
Sheep infected with maedi-visna virus experience immunological disorders leading to progressive chronic diseases involving the brain, lung, spleen, and lymph nodes. To study the biological activity of the viral transactivating Tat protein, we generated transgenic mice carrying the tat gene. Analysis of the transgenic mouse tissues for tat mRNA revealed that while low at the messenger level, the expression of the transgene correlated with dramatic follicular lymphoproliferative disorders involving the lung, spleen, lymph nodes, and skin. This finding suggests that the viral protein possesses a high pathological potency. Our findings show that the maedi-visna virus tat gene product contributes to the pathogenesis of multiorgan proliferative disorders associated with maedi-visna virus infection.